EMOTIONAL STIMULI, ENGAGEMENT AND IMPULSE BUYING IN SOCIAL COMMERCE: EVIDENCE FROM UKRAINE - Бойко, Наталя Олександрівна (Current Problems of Sustainable Development, 2026)
This study investigates how emotional stimuli in social commerce influence impulse buying behaviour in Ukraine, with particular attention to the mediating roles of emotional arousal and consumer engagement in a context of economic uncertainty. A quantitative cross-sectional design is employed, based on an online survey of Ukrainian consumers (N = 620) who have made purchases via social commerce platforms. The conceptual model is grounded in the Stimulus–Organism–Response (S-O-R) framework. Data are analysed using partial least squares structural equation modelling (PLS-SEM) to assess measurement reliability, validity and structural relationships. The findings show that emotional stimuli—such as time pressure, social proof and sensory-rich content—significantly enhance both consumer engagement and emotional arousal. These factors, in turn, increase the urge to buy impulsively and lead to actual impulse buying behaviour. Consumer engagement plays a dual role, acting both as a mediator and as a direct predictor of behavioural outcomes. Perceived risk exhibits a negative, albeit weaker, effect on impulse buying. From a managerial perspective, the results suggest that marketers should combine emotional triggers with engagement-oriented strategies while maintaining trust, transparency and data privacy—particularly in high-uncertainty environments such as Ukraine. This study contributes to the social commerce literature by extending the S-O-R framework through the integration of engagement and emotional mechanisms in an under-researched Eastern European context, offering both theoretical refinement and practical implications.
Keywords: social commerce; impulse buying behaviour; emotional stimuli; consumer engagement; social media; Ukraine